THE USE OF ANIMATION CLIPS AS MEDIA IN TEACHING WRITING - Huda, Moh Choirul (TELL - US JOURNAL, 2019)
This study is aimed at describing: (1) the implementation of animation clips as a media in teaching writing to the eleventh grade students of Madrasah Aliyah (MA) Sunan Giri Gondang in academic year 2017/2018, (2) how is the students’ writing score after being taught using Animation clips, (3) problems faced by the teacher in teaching writing using animation clips. This research is a descriptive qualitative research. The subjects are the teacher and the eleventh grade students of MA Sunan Giri Gondang in academic year 2017/2018 totally 20 students. The instruments used in this research are test, observation checklist, and interview guide. The result shows that the implementation of animation clips in teaching writing is successful. The students’ writing score is getting better after being taught using Animation clips. The mean score in pre-test is 74 while in post-test is 79. Applying Animation clips in writing class has many advantages such as the class is easy to manage, the students feel free to select the writing topic, etc. However, there are some problems faced by the teacher which result the disadvantages of this media in teaching writing such as the teacher and the students should be very familiar with ICT, the activity should be conducted at computer lab, the teacher finds difficulties in creating animation herself, etc.